Asymmetric Responses of Stock Prices to Money Supply and Oil Prices Shocks in Turkey: New Evidence from a Nonlinear ARDL Approach - Altintas, Halil; Yacouba, Kassouri (International Journal of Economics and Financial Issues, 2018)
This study investigates how stock market prices react to oil prices and money supply shocks in Turkey using a nonlinear ARDL approach. We establish the time series properties of the data using both conventional linear unit root tests and the procedure advanced by Zivot-Andrews (1992) to consider the possible existence of endogenous break in the series. Empirical evidence revealed asymmetric cointegration through Wald statistics of Pesaran and Banerjee. Findings suggest asymmetric responses of Turkish stock market prices to oil prices and money supply shocks, confirming the importance of non-linearity in macro-finance variables. Namely, in the long-run, we find a significant negative relation between oil prices and stock market prices. Meanwhile, stock market prices react positively to negative (positive) shocks in money supply. The obtained evidence of the asymmetric behaviors of stock prices should be taken into account by stock market participants when dealing with their portfolio diversification strategies. Keywords: Stock Price, Oil Price, Money Supply. JEL Classifications : C58, E44, E52, Q43.